The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fcimb.2020.545372
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Clinical Studies of Inactivated Polyvalent HFRS Vaccine

Abstract: Hemorrhagic fever with renal syndrome (HFRS) is the most common natural focal disease in the Russian Federation with about 6–12 thousand cases annually. 97.7% of all HFRS cases in Russia are caused by the Puumala virus, 1.5%—by the Hantaan, Amur, Seoul viruses, and about 0.8% by the Kurkino and Sochi viruses. There are no licensed vaccines for the prevention of HFRS in the European Region; there are no specific therapeutic to treat orthohantavirus infections. Here we report the results of candidate polyvalent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Antibodies were detectable 33 months after vaccination. Recently, pre-clinical studies of inactivated polyvalent HFRS vaccine demonstrated the activation of a balanced immune response to PUUV, HNTV, and DOBV [ 190 ].…”
Section: Vaccines and Prevention Of Hantavirus Infectionsmentioning
confidence: 99%
“…Antibodies were detectable 33 months after vaccination. Recently, pre-clinical studies of inactivated polyvalent HFRS vaccine demonstrated the activation of a balanced immune response to PUUV, HNTV, and DOBV [ 190 ].…”
Section: Vaccines and Prevention Of Hantavirus Infectionsmentioning
confidence: 99%
“…A complex of virological, immunological and molecular genetic methods was used to detect orthohantaviruses and specific antibodies in HFRS patients and small mammals [35,39,45,[57][58][59].…”
Section: Specific Laboratory Diagnostics Of Hfrsmentioning
confidence: 99%
“…IL-6 непосредственно участвует в стимуляции пролиферации В-клеток и активации тромбоцитопоэза. В совокупности, повышенный уровень указанных выше цитокинов в сыворотке крови пациентов обеспечивает активацию иммуногенных реакций с участием лимфоцитов типа Th1, а также стимуляцию процесса образования тромбоцитов [23]. Лабораторные данные подтверждают эти данные: у пациентов с ГЛПС обнаружены циркулирующие CD8 + лимфоциты, повышенный уровень в сыворотке крови антител к хантавирусу, а также признаки активации тромбоцитопоэза.…”
Section: обзорunclassified